2008
DOI: 10.1007/s00127-008-0409-y
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders and mental health care in Canada and Australia: comparative epidemiological findings

Abstract: Causation cannot be determined from this study but possible explanations for differences in prevalence include changes in global economic, political and security contexts and concerns between 1997 and 2002 and the possible role of greater availability of alcohol in Australia. The findings also provide encouragement that strenuously implementing a national mental health policy may have been of benefit to people with mental health problems in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 49 publications
0
26
1
1
Order By: Relevance
“…In comparison to previous research [23,24], the study revealed that the proportion of persons affected by a mental disorder in a 12-month period and who used healthcare services was relatively high (near 50%). The proximity of a psychiatric hospital may account for the high mental healthcare service use recorded in the catchment area.…”
Section: Discussioncontrasting
confidence: 82%
“…In comparison to previous research [23,24], the study revealed that the proportion of persons affected by a mental disorder in a 12-month period and who used healthcare services was relatively high (near 50%). The proximity of a psychiatric hospital may account for the high mental healthcare service use recorded in the catchment area.…”
Section: Discussioncontrasting
confidence: 82%
“…Previous studies have reported that severe mental disorder cases were associated with more intensive service utilization than mildly severe or moderate cases (Tempier et al, 2009;.…”
Section: Determinants Of Service Utilization Of Patient With Mental Dmentioning
confidence: 91%
“…Individuals with concurrent mental disorder and substance abuse usually reported the highest utilization rates, and the least favorable selfperception/assessment of good health (Rush et al, 20010). Substance abuse alone is related to very low service utilization (Tempier et al, 2009). Attitudes and beliefs regarding mental disorder and treatment also play a role in service utilization.…”
Section: Determinants Of Service Utilization Of Patient With Mental Dmentioning
confidence: 99%
“…Au Canada et en France, les troubles mentaux affectent annuellement 15 % et 18 % de la population respectivement ; sur le plan international, de 4,3 % (Chine) à 26,4 % (États-Unis) (Chevreul, Prigent, Bourmaud, Leboyer et Durand-Zaleski, 2013 ;Kisely, 2009). Les études internationales estiment qu'environ essentiellement le tiers des personnes diagnostiquées avec des troubles mentaux consulteraient pour raison de santé mentale (Andrews, Henderson et Hall, 2001 ;Andrews, Issakidis et Carter, 2001 ;Tempier et al, 2009). La documentation met aussi en relief, pour plusieurs troubles mentaux, l'adéquation non optimale des traitements, le délai important de prise en charge après les premiers symptômes de la maladie, les duplications de services et les difficultés d'accès et de continuité de soins (Howell, Marshall, Opolski et Newbury, 2008 ;WHO/Wonca, 2008 Les troubles mentaux sont souvent divisés en troubles mentaux courants (ex.…”
Section: Résumé De L'articleunclassified